Hermeneutics as Andenken or "remembering thinking" : A reading from Gianni Vattimo - Minaya, Edickson (2025)
Starting from Gianni Vattimo's reading, the article exposes his conception of hermeneutics as Andenken or “remembering thinking.” The idea we defend is that the Italian philosopher practices hermeneutics under the motto of “recovering tradition”, although questioning it and providing arguments for its renewal, a thesis that he inherits from Heidegger and Gadamer. It follows that the true work of hermeneutics is to propose interpretive models that integrate our relationship with the world, hence remembering tradition plays a vital role in this work.